Association between somatic microsatellite instability, hypermutation status, and specific T cell subsets in colorectal cancer tumors - Thomas, Claire E.; Takashima, Yasutoshi; Wesselink, Evertine; Ugai, Tomotaka; Steinfelder, Robert S.; Buchanan, Daniel D.; Qu, Conghui; Hsu, Li; Dias Costa, Andressa; Gallinger, Steven; Grant, Robert C.; Huyghe, Jeroen R.; et al. (Frontiers in Immunology, 2024)
BackgroundMicrosatellite instability-high (MSI-high) tumors comprise ~15% of sporadic colorectal cancers (CRC) and are associated with elevated T cell infiltration. However, the universality of this response across T cell subtypes with distinct functions is unknown.MethodsIncluding 1,236 CRC tumors from three observational studies, we conducted in-situ T cell profiling using a customized 9-plex (CD3, CD4, CD8, CD45RA, CD45RO, FOXP3, KRT, MKI67, and DAPI) multispectral immunofluorescence assay. MSI status was assessed through polymerase chain reaction or immunohistochemical assays. We used multivariable ordinal logistic regression to estimate odds ratios (OR per increasing quantile) and 95% confidence intervals (CIs) for the association of MSI status with quantiles of T cell densities in either tumor epithelial or stromal tissue areas.ResultsCompared to microsatellite instability low or microsatellite stable (MSI-low/MSS) tumors, MSI-high status was associated with higher density for the majority of immune subsets (twelve out of eighteen) in both epithelial and stromal tissue areas. The strongest associations were for CD3+CD8+ T cells in epithelial areas [OR (95% CI) for naive, memory, and regulatory subsets = 3.49 (2.57, 4.75); 2.82 (2.10, 3.78); 3.04 (2.24, 4.13), respectively]. Conversely, stromal area CD3+CD4+ memory T cells were inversely associated [OR (95% CI) = 0.68 (0.51, 0.91)].DiscussionMSI-high status was strongly associated with higher densities of most T cell subsets in both epithelial and stromal tissue areas. Our investigation supports efforts to identify patients who may be more likely to respond to current immunotherapy treatments.SignificanceThis study helps us better understand how a clinically relevant tumor phenotype, microsatellite instability status, is related to different functioning T cell densities in colorectal tumors, which may impact future immunotherapy strategies.